Niceville - Stroud, Carsten (North Sydney, N.S.W. : Random House Australia, 2012)
Welcome to Niceville, a sleepy, old-fashioned hamlet in America's Deep South. But don't be fooled by its pleasant exterior. 'Stephen King meets Twin Peaks' in this chilling thriller with a horror twist... When ten-year-old Rainey Teague disappears on his way home from school, Detective Nick Kavanaugh and his team are baffled. CCTV shows Rainey staring into the window of a pawn shop - he's there one minute and simply gone the next. And that is only the beginning of the nightmare as a chain of terrifying events has been triggered in idyllic Niceville. As Nick struggles to uncover what happened to Rainey, his investigation takes him deep into the history of Niceville and it soon becomes clear that there's a much higher than average rate of abductions in this town. And there'll be more victims to come.
Imprint: RHA eBooks Adult.
Audience: General.
Issued also in printed form.
Mode of access: Internet. Refer to the publisher's home page.
Keywords: Married people -- Fiction; Missing children -- Fiction; Fiction - General; Modern & contemporary fiction (post c 1945); Australian